2018
DOI: 10.1152/ajpheart.00365.2017
|View full text |Cite
|
Sign up to set email alerts
|

Nitrosative stress uncovers potent β2-adrenergic receptor-linked vasodilation further enhanced by blockade of clathrin endosome formation

Abstract: This study investigated the effect of sodium nitroprusside (SNP) preexposure on vasodilation via the β-adrenergic receptor (BAR) system. SNP was used as a nitrosative/oxidative proinflammatory insult. Small arterioles were visualized by intravital microscopy in the hamster cheek pouch tissue (isoflurane, n = 45). Control dilation to isoproterenol (EC: 10 mol/l) became biphasic as a function of concentration after 2 min of exposure to SNP (10 M), with increased potency at picomolar dilation uncovered and decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
(59 reference statements)
0
5
0
Order By: Relevance
“…To the best of our knowledge, the exact molecular pathway mediated by β2-AR in retinal vessels is still elusive. It was reported that in ischemia the behavior of β2-AR varied: whereas a subgroup was internalized, a second group showed an alternate desensitization that finally caused an increase in affinity [ 46 ]. This in vitro observation supports our hypothesis of a link between β2-agAAb (via β2-AR) and impaired retinal microcirculation in glaucoma eyes.…”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, the exact molecular pathway mediated by β2-AR in retinal vessels is still elusive. It was reported that in ischemia the behavior of β2-AR varied: whereas a subgroup was internalized, a second group showed an alternate desensitization that finally caused an increase in affinity [ 46 ]. This in vitro observation supports our hypothesis of a link between β2-agAAb (via β2-AR) and impaired retinal microcirculation in glaucoma eyes.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, recent experimental evidence indicates that nitrotyrosine may induce unexpected vasodilatory response to β-adrenergic agonists through blocking of β2 adrenergic receptor internalization at nerve endings. 56 Interestingly, CPT may induce vasodilation through stimulation of postjunctional β2 adrenoceptors 51 and could, therefore, be enhanced by increased NTY local concentrations. Thus, the effect of local concentrations of NTY on paradoxical vasodilation by CPT observed in our AL population should be further explored.…”
Section: Discussionmentioning
confidence: 99%
“…One of these confirmed partners is the Promoter of RNA-induced silencing, C3PO 24 , 25 , which is inhibited by PLCβ1 binding 3 , 26 28 . In recent work, we characterized the proteins bound to cytosolic PLCβ1 in undifferentiated PC12 cells and found roughly 30% of bound proteins are identified as stress granules proteins, including Ago2, PABPC, eIF5a and G3BP1 4 , 29 . These studies showed that reducing the cytosolic level of PLCβ1 either by down-regulation, osmotic stress or Gαq activation allowed for the release of bound proteins and promoted the formation of stress granules.…”
Section: Discussionmentioning
confidence: 99%